Homogeneous Modification of Sugarcane Bagasse by Graft Copolymerization in Ionic Liquid for Oil Absorption Application. (29th August 2016) - Chen, Ming-Jie; Zhang, Xue-Qin; Liu, Chuan-Fu; Shi, Qing-Shan
Abstract : Sugarcane bagasse, lignocellulosic residue from the sugar industry, is an abundant and renewable bioresource on the earth. The application of ionic liquids in sugarcane bagasse biorefinery is gaining increasing interest. The homogeneous modification of sugarcane bagasse by free radical initiated graft copolymerization of acrylate monomers using 1-allyl-3-methylimidazolium chloride as solvent was performed. A variety of sugarcane bagasse graft copolymers with different weight percent gain were prepared via adjusting the monomer dosage. FT-IR studies confirmed the success in attaching the poly(acrylate) side chains onto sugarcane bagasse. Oil absorbency studies suggested that the sugarcane bagasse graft copolymers were potential biobased materials for effective treatment of ester-based oils. SEM studies showed that the sugarcane bagasse graft copolymers displayed a dense morphology structure. Thermogravimetric analysis demonstrated that the thermal stability of sugarcane bagasse decreased after the homogeneous modification by the graft copolymerization. The present study provides an alternative strategy to convert sugarcane bagasse into a value-added functional biobased material.